(untitled) (Nóema, 2022)
In this article, I will discuss how Radical Empiricism, conceived together with James’ pragmatism and Whitehead’s speculative method, operates a decentralization of the role of human consciousness in the process of constructing the real. This operation, which focuses on the pivotal role of relations for the co-constitution of all the entities with the environments, can be a useful tool for rethinking eco-political pragmatics within the precarious era of socio-climatic crisis. W.’s speculative method and J.’s pragmatism, which assume an absolute experience as the immanent product of a set of relations/flows and matter, place thinking, objects, imaginaries and living things, including the human, in a process of constant and mutual constitution of reality. The experience of radical empiricism, accompanied by pragmatism and speculative method, can become in this direction a tool for composing new ideas that can engage with the real to recreate new environments together with the living and non-living with whom the human shares life on earth.